Perilaku Pemakaian Plastik Sekali Pakai oleh Mahasiswa dalam Aktivitas di Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mataram - Auliya, Baiq Yuni Ariati; Pibiputri, Heppy Tasya; Supriyadi, Royan; Supardiono, Supardiono; Dujana, Lalu Muhammad Aby (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Single-use plastic remains a major pollution problem in the campus environment. This study aims to analyze the single-use plastic consumption behavior of students in the Faculty of Mathematics and Natural Sciences (FMIPA) at the University of Mataram based on the Theory of Planned Behavior (TPB), including attitudes, subjective norms, perceived behavioral control, intentions, and actual behavior. This study used a descriptive quantitative approach, with 94 students selected through stratified random sampling from six study programs as respondents. Data were collected using a 1–5 Likert scale questionnaire and analyzed descriptively. The results showed that all TPB constructs tended to be in the moderate category, indicating that environmental awareness has been established but has not yet developed into consistent behavioral habits. A similar trend was seen across attitudes, subjective norms, perceived behavioral control, and actual behavior. The Environmental Science Study Program consistently scored higher than other study programs, indicating that an ecologically based academic culture plays a crucial role in establishing stronger social norms, thus enabling environmentally conscious behavior to be realized.